#TITLE_ALTERNATIVE# - ASMA REVI ( NIM : 10511103 ), UMMI
Zinc is one of heavy metals that at excessive concentration level could cause environmental and health problems. Normally, determination of zinc was conducted using atomic absorption spectrophotometry (AAS) method. However this method needs large and complicated equipment so that it cannot be used for field analysis. Anodic stripping voltammetry (ASV) method can be used for field analysis because it only requires simple and small equipment. However most of ASV methods for heavy metal determination require mercury electrodes. In this study we developed mercury-free working electrode for zinc determination with ASV method. For this purpose, carbon paste electrode (CPE) was modified with lignosulphonate. The lignosulphonate was trapped on the surface of CPE through electropolymerization of 3-aminophenol from solution containing mixture of 3-aminophenol and lignosulphonate. Optimum stripping current was obtained with 180 seconds deposition time at −1.3 V deposition potential in acetate buffer pH 5 supporting electrolyte solution. Under the optimum condition, a linear response was observed in the concentration range of 0.01 to 1.00 mM with detection limit of 7.9 μM. The repeatability of measurement gave a %RSD of 3.94% (n=15). Determination of zinc in real samples (anti-dandruff shampoo) with the developed method was very accurate %recovery of 101.31% and 99.90 and the results were in accordance with those of AAS method.